PENINGKATAN SUMBER DAYA MANUSIA PENGELOLA PENCATATAN ZAKAT DALAM PEMBANGUNAN EKONOMI MAKRO - Mirza Hisyam Maulana; Fauzatul Laily Nisa (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This research aims to reveal methods for increasing human resources for recording and managing zakat in an effort to increase macroeconomic growth in Indonesia. The research method is in the form of a descriptive method or an elaboration method with a type of qualitative research based on the phenomenon of human resource development for zakat managers in Indonesia who have insufficient work competency. The data collection technique uses note-taking techniques on data in the form of sentence descriptions or other data that supports research needs. The data analysis model uses the Miles and Huberman analysis model which consists of three actions, namely data reduction, data presentation, and determining initial conclusions. The research results reveal that actions to increase Human Resources in zakat management are carried out with assistance from superiors in zakat institutions in terms of employee introduction, training and work processes, provision of performance facilities and infrastructure that support employee performance, as well as incentives. Accurately recording, managing and distributing zakat has the impact of increasing macroeconomic growth due to four things, namely income distribution, economic empowerment of the people, social investment, and increased consumption and investment.